2021
DOI: 10.1097/jwh.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Comfort Level of Current Physical Therapist Students in Addressing Sexual Issues With Patients

Abstract: Background: Scarce evidence has been found on factors that determine physical therapist (PT) students' comfort level in addressing sexual issues with patients. Determining influential factors and barriers may help educators adjust their curriculum to better prepare students. Objectives: To identify the comfort level of PT students in addressing sexual issues with patients, demographic factors that impact the students' comfort level, and barriers to PT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…11 A recent study of physical therapist (PT) students' comfort levels indicated that less than 50% of respondents felt they possessed the necessary skills to address sexual issues and only 23.6% were likely to initiate discussions with patients indicating a potential link between confidence and initiation. 12 Other studies of PTs' comfort levels have demonstrated similar results, 13,14 which is a concern as PTs often provide care to patients who are recovering from various medical conditions that can affect a patient's sexual health.…”
Section: Review Of Literaturementioning
confidence: 85%
See 4 more Smart Citations
“…11 A recent study of physical therapist (PT) students' comfort levels indicated that less than 50% of respondents felt they possessed the necessary skills to address sexual issues and only 23.6% were likely to initiate discussions with patients indicating a potential link between confidence and initiation. 12 Other studies of PTs' comfort levels have demonstrated similar results, 13,14 which is a concern as PTs often provide care to patients who are recovering from various medical conditions that can affect a patient's sexual health.…”
Section: Review Of Literaturementioning
confidence: 85%
“…The survey was consistent with one used in a previous study, 12 which was originally based on a survey created by Abraham et al 18 Minor edits were made to reflect both OT- and PT-specific education. For example, clinical education experience was edited to include fieldwork, and clinical instructor to include preceptor.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations